Um estudo longitudinal de tempo e aspecto na demência do tipo Alzheimer - Nespoli, Juliana Barros; Novaes, Celso Vieira (Letras de Hoje, 2016)
O objetivo deste estudo é investigar possíveis alterações na expressão linguística de tempo e aspecto de pacientes portadores da demência do tipo Alzheimer (DTA). Principalmente, objetiva-se contribuir para o entendimento acerca do comprometimento cognitivo subjacente a essas eventuais alterações. Para tanto, foi desenvolvido um estudo de caso de caráter longitudinal. Foi selecionado um paciente portador da DTA, que foi submetido a quatro aplicações de duas avaliações de naturezas distintas: uma avaliação neuropsicológica e uma avaliação linguística. Foram detectadas alterações na expressão linguística de tempo e aspecto. A análise desses resultados sugere que as alterações detectadas até a terceira aplicação podem decorrer de um comprometimento no sistema linguístico ou em sistemas não linguísticos. Já o declínio na expressão linguística de tempo e aspecto detectado na quarta aplicação sugere um comprometimento no sistema linguístico. ******************************************************************** A longitudinal study of tense and aspect in the dementia of the Alzheimer type Abstract: This study aims to investigate any possible impairment related to the linguistic expression of tense and aspect by patients with the dementia of the Alzheimer type (DAT). Mainly, it aims to contribute to the understanding of the cognitive disruption underlying these eventual impairments. In order to achieve these aims, it was developed a case study of longitudinal nature. It was selected a DAT patient, who was submitted four times to two different evaluations: a neuropsychological evaluation and a linguistic evaluation. Impairments in the linguistic expression of tense and aspect were detected. The analysis of the results suggests that the impairments detected up to the third assessment may have been originated due to a disruption of the linguistic system or of non-linguistic systems. The decline in the linguistic expression of tense and aspect detected in the fourth assessment suggests a disruption of the linguistic system. Keywords: Tense; Aspect; Dat; Longitudinal study